2013
DOI: 10.7897/2321-6328.01413
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Selection Criteria in Rice

Abstract: Genetic parameters, correlation and path analysis for 12 yield and quality traits were studied during rabi, 2009-10 in 21 genotypes of rice. High estimates of GCV were recorded for plant height, number of filled grains/panicle and grain yield/plant. Heritability in broad sense was high for all the characters except spikelet fertility. High heritability coupled with high genetic advance as per cent mean were recorded for number of productive tillers/plant, panicle density, number of filled grains/panicle, 1000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 3 publications
23
10
1
Order By: Relevance
“…The phenotypic coefficients of variability (14.57%) were non-significantly higher than that of the genotype (14.07%) in fertility percentage, indicating that the variation is due to genetic content, with minimal involvement of the environment. Similar results were reported by Vanisree et al (2013), who observed a slightly higher phenotypic than genotypic coefficient of variation in fertility percentage. The estimation of high broad sense heritability (93.1%) in fertility percentage reflected the ease of selection during an earlier generation (Vanisree et al, 2013).…”
Section: Fertility Percentagesupporting
confidence: 90%
See 2 more Smart Citations
“…The phenotypic coefficients of variability (14.57%) were non-significantly higher than that of the genotype (14.07%) in fertility percentage, indicating that the variation is due to genetic content, with minimal involvement of the environment. Similar results were reported by Vanisree et al (2013), who observed a slightly higher phenotypic than genotypic coefficient of variation in fertility percentage. The estimation of high broad sense heritability (93.1%) in fertility percentage reflected the ease of selection during an earlier generation (Vanisree et al, 2013).…”
Section: Fertility Percentagesupporting
confidence: 90%
“…Similar results were reported by Vanisree et al (2013), who observed a slightly higher phenotypic than genotypic coefficient of variation in fertility percentage. The estimation of high broad sense heritability (93.1%) in fertility percentage reflected the ease of selection during an earlier generation (Vanisree et al, 2013).…”
Section: Fertility Percentagesupporting
confidence: 90%
See 1 more Smart Citation
“…Filled grains per panicle had high positive indirect effect on grain yield through effective tillers, plant height, panicle length, flag leaf length, flag leaf width. Similar results were reported by Vanisree et al (2013) for effective tillers, plant height, panicle length and Vinodini et al (2005) for test weight.…”
Section: Path Coefficient Analysissupporting
confidence: 89%
“…This possibly occurred because of the genotypes used and the environmental conditions under which the study was conducted. Other authors reported low heritability for Percentage spikelets fertility per plant in rice (Vanisree et al, 2013 andAnyanwu andObi, 2014). The results obtained from regression analysis revealed that additive gene effect (a) only was significant for percentage spikelets fertility per plant; while dominance gene effect (d) and epistasis (aa), (ad) as well (dd) were not significant.…”
Section: Discussionmentioning
confidence: 96%